Exercise rescues the immune response fine‐tuned impaired by peroxisome proliferator‐activated receptors γ deletion in macrophages. Issue 4 (21st September 2018) - Silveira, Loreana Sanches; Batatinha, Helena Angélica Pereira; Castoldi, Angela; Câmara, Niels Olsen Saraiva; Festuccia, Willian T.; Souza, Camila Oliveira; Rosa Neto, José Cesar; Lira, Fábio Santos
Abstract: Background: Exercise is a powerful tool for prevention and treatment of many conditions related to the cardiovascular system and also chronic low‐grade inflammation. Peroxisome proliferator‐activated receptors γ (PPARγ) exerts an import role on the regulation of metabolic profile and subsequent inflammatory response, especially in macrophages. Purpose: To investigate the effects of 8‐week moderate‐exercise training on metabolic and inflammatory parameters in mice with PPARγ deficiency in myeloid cells. Methods: Twelve‐week old mice bearing PPARγ deletion exclusively in myeloid cells (PPARγlox/lox Lys Cre −/+, knockout [KO]) and littermate controls (PPARγlox/lox Lys Cre −/−, wild type [WT]) were submitted to 8‐week exercise training (treadmill running at moderate intensity, 5 days/week). Animals were evaluated for food intake, glucose homeostasis, serum metabolites, adipose tissue and peritoneal macrophage inflammation, and basal and stimulated cytokine secretion. Results: Exercise protocol did not improve glucose metabolism or adiponectin concentrations in serum of KO mice. Moreover, the absence of PPARγ in macrophages exacerbated the proinflammatory profile in sedentary mice. Peritoneal cultured cells had higher tumor necrosis factor‐α (TNF‐α) secretion in nonstimulated and lipopolysaccharide (LPS)‐stimulated conditions and higher Toll‐4 receptor (TLR4) gene expression under LPS stimulus. Trained mice showed reduced TNF‐α content in adipose tissue independently of the genotype. M2 polarization ability was impaired in KO peritoneal macrophages after exercise training, while adipose tissue‐associated macrophages did not present any effect by PPARγ ablation. Conclusion: Overall, PPARγ seems necessary to maintain macrophages appropriate response to inflammatory stimulus and macrophage polarization, affecting also whole body lipid metabolism and adiponectin profile. Exercise training showed as an efficient mechanism to restore the immune response impaired by PPARγ deletion in macrophages. Abstract : PPARγ seems to maintain macrophages appropriate response to inflammatory stimulus and macrophage polarization. Exercise training was an efficient mechanism to restore the immune response impaired by PPARγ deletion in macrophages.